Chagas Disease in Dogs - María Elizabeth Márquez Contreras (Journal of Veterinary Healthcare, 2018)
Chagas disease is zoonotic illness or an anthropozoonosis caused by flagellated protozoan parasite Trypanosoma cruzi. This infection presents alarming rates of incidence/prevalence, for this reason, is recognized worldwide as one of the 13 most neglected tropical diseases 1. Numerous studies have demonstrated the existence of domestic dogs infected with T. cruzi across endemic areas ranging from southern United States of America to Argentina 2. The reported prevalence varies widely (1.42-92%), depending on ecoepidemiological and sociocultural factors 3. It is important to emphasize that the natural infection in dogs with T. cruzi occurs in the same way as in humans, that is to say, through active transmission by vectors, contamination by feces infected with the parasite through wounds or the conjunctiva, can also occur by ingestion of infected vectors or tissues of wild animals present in the peridomicile or home 4. The transplacental transmission is also an important mode of transmission in dogs 5. Nevertheless, the main mode of transmission in canine species seems to be the ingestion of infected vectors 6. During the life cycle of T. cruzi the trypomastigotes present in the heces of the triatomines are introduced in the mammalian host by contamination of the insect bite or mucosal membranes. The metacyclic form can penetrate a variety of phagocytic and nonphagocytic nucleated cells. Once inside the cells the parasite becomes in amastigote, which are multiplicative forms that divide into cells. Due to the high parasitic load they produce the lysis of the cells and escapes into the cytoplasm. The amastigotes transform to slender trypomastigotes which can invade adjacent cells, this forms can be ingested by triatomines and they transform into epimastigotes Finally, after migration to the bug's hindgut, the epimastigotes differentiate into infectious metacyclic trypomastigotes, in this way the life cycle of this microorganism is completed 7.
Keywords: Anthropozoonosis